2017
DOI: 10.1016/j.ddtec.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The production of 3D tumor spheroids for cancer drug discovery

Abstract: New cancer drug approval rates are ≤ 5% despite significant investments in cancer research, drug discovery and development. One strategy to improve the rate of success of new cancer drugs transitioning into the clinic would be to more closely align the cellular models used in the early lead discovery with pre-clinical animal models and patient tumors. For solid tumors, this would mandate the development and implementation of three dimensional (3D) in vitro tumor models that more accurately recapitulate human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
284
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(320 citation statements)
references
References 48 publications
8
284
0
4
Order By: Relevance
“…We observed four classic morphologies presented in the 3D cultured spheroids with peptide hydrogel scaffolds: round, mass, grape, and stella, as shown in Figure 1B, which is consistent with the literature report 53,54 . Confocal fluorescence image was further used to confirm the round tumor-like morphology in Figure 1C, which exhibits the typical in vivo tumor-like tissue architecture 55 with each round cells laid over to form tumor spheroid. Figure 1C is a 3D confocal imaging reconstruction of cervical tumor cell spheroid using our 3D culture method.…”
Section: Ev Secretion Dynamics From 3d Cultured Cells Significantly Dmentioning
confidence: 97%
“…We observed four classic morphologies presented in the 3D cultured spheroids with peptide hydrogel scaffolds: round, mass, grape, and stella, as shown in Figure 1B, which is consistent with the literature report 53,54 . Confocal fluorescence image was further used to confirm the round tumor-like morphology in Figure 1C, which exhibits the typical in vivo tumor-like tissue architecture 55 with each round cells laid over to form tumor spheroid. Figure 1C is a 3D confocal imaging reconstruction of cervical tumor cell spheroid using our 3D culture method.…”
Section: Ev Secretion Dynamics From 3d Cultured Cells Significantly Dmentioning
confidence: 97%
“…Anticancer activity in 3D multicellular spheroids 3D multicellular tumor spheroids (MCTSs) are used to simulate the in vivo tumor microenvironment and provide higher complexity than the standard 2D monolayer cultures due to their physiological relevance to solid tumors. [26,27] Therefore, to validate the antitumor activity of the synthesized gold complexes in an in vivo tumore nvironment, cervical cancerc ells (HeLa) were grown in ultra-low attachment (ULA) plates for 2days to generate3 Dm ulticellulars pheroids, which weret hen treated with the IC 50 concentrationsoft he gold complexes. Figure 9s hows the morphological changes in the MCTSs after 72 ho ft reatment with the gold complexes.…”
Section: Interaction With Human Serum Albumin (Hsa)mentioning
confidence: 99%
“…Analysis of these spheroids revealed that the only viable cells existed 200 μm from the surface of construct, while inside the sphere, all cells were dead, presumably due to nutrient and oxygen unavailability. It has been reported that nuclei are undetectable at 150–200 μm from the surface of such constructs due to necrosis . Using the layer‐by‐layer technique, cells located >5 cell layers undergo induced necrosis .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nuclei are undetectable at 150-200 μm from the surface of such constructs due to necrosis. 25,26 Using the layer-by-layer technique, cells located >5 cell layers undergo induced necrosis. 27 Thus, our results were in agreement with these previous studies.…”
Section: Discussionmentioning
confidence: 99%